The hybridity of romantika / Nurul Syahirah Muhamad Mohktar - Muhamad Mohktar, Nurul Syahirah (2013)
This study investigated the hibridity of Romantika which is the impact of a brand identity and advertising on consumer perceptions. The research problem is to establish the difference between the perceptions of the brand, namely the brand image and the brand identity that the company wishes to establish. Using a case study design , I gathered data using written questionnaire, oral questionnaire (interview) and Romantika Home Decor observation. Consumer at Romantika Home Decor has been selected . The research examines the feedback of brand identity of Romantika Home Decor. Additionally, I interviewed the consumer about experiences in using product of Romantika Home Decor. The result of data collection shows that consumer of Romantika 's product has been selected. The research examines the feedback of brand identity and advertising of Romantika. Additionally , I interviewed the consumer that using Romantika's product and distributed the questionnaire in Malacca. The first chapter introduced the topic and related aspects of the thesis. It included a brief description of In chapter two the problem analysis will be presented , as well as the main research question and the sub research questions. Chapter one serves as the theoretical foundation of the research. Literature about the concepts brand identity , brand image and brand alignment will be discussed. The chapter deals with defining the concepts, and concludes with a proposed research model that will be applied. The proposed model is based on an alignment framework by Srivastava & Thomas (2010). The purpose is to illustrate the relationship between a company's, channel partners ' and consumer's perspective on a brand. The brand identity prism of Kapferer (2008) will be used to identify these perspectives.